(untitled) (London Journal of Research In Science: Natural and Formal, 2025)
Latin-American has a great biodiversity, probably the richer in the planet: Brazil, Colombia and Mexico are the three nations that involves the greatest area of green forest. The South American countries include the Amazonas river that is an extraordinary ecosystem plethoric of life. Mexico has four of the five macroclimates, it includes as hot as the habitat of desert to the rainy jungles or cloudy forests; in addition, this region has an important agriculture tradition that comes from pre-Columbian times. Unfortunately, a bad territorial planification are the reason that the cities and bad agricultural practices have devastated natural ecosystems, causing a desertification of the territory. The people and lot of civil organizations have done multiple efforts to impulse permaculture practices in many Latin-American countries in hope of better perspectives to society and to the planet as a whole.